An Additional Prior Retrieval Alters the Effects of a Retrieval-Extinction Procedure on Recent and Remote Fear Memory - An, Xianli; Yang, Ping; Chen, Siguang; Zhang, Fenfen; Yu, Duonan (Frontiers in Behavioral Neuroscience, 2018)
Several studies have shown that the isolated retrieval of a consolidated fear memory can induce a labile phase, during which extinction training can prevent the reinstatement, a form of relapse in which fear response to a fear-provoking context returns when a mild shock is presented. However, fear memory retrieval may also have another opposing result: the enhancement of fear memory. This implies that the fear memory trace can be modified by a brief retrieval. Unclear is whether the fear-impairing effect of retrieval-extinction (RE) is altered by a prior brief retrieval. The present study investigated the responses of recent and remote fear memories to the RE procedure after the presentation of an additional prior retrieval (priRet).A single RE procedure effectively blocked the reinstatement of 2-day recent contextual fear memory. The memory-impairing effect of the RE procedure was not observed when priRet was presented 6 or 24 h before the RE procedure. In contrast to the 2-day recent memory, the RE procedure failed to block the reinstatement of 36-day remote fear memory but successfully disrupted the return of remote fear memory after priRet. This memory -disruptive effect on remote memory did not occur when priRet was performed in a novel context. Nimodipine administration revealed that the blockade of priRet-induced processes recovered the effects of the RE procedure on both recent and remote fear memories. Our findings suggest that the susceptibility of recent and remote fear memories to RE procedures can be altered by an additional retrieval.